The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.18203/2349-3291.ijcp20172609
|View full text |Cite
|
Sign up to set email alerts
|

A study of clinical and hematological profile of children with sickle cell disease in a tertiary care hospital, Valsad, India

Abstract: Background: Sickle cell disease is commonly seen in rural population of south part of Gujarat in India. It is one of the common causes of recurrent hospitalization, morbidity and mortality in pediatric population. This study was therefore undertaken to evaluate the clinical profile of sickle cell disease in a tertiary care hospital.Methods: This was the prospective observational study done from November 2015 to October 2016. All the hospitalized diagnosed case of sickle cell disease and trait in age group of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…A comparable outcome was recorded among akin participants in North Maharashtra, India, where low levels of Hb concentration, RBC count, and PCV was documented [25]. Likewise, Patel and colleagues [26] also reported significant low level of hemoglobin and HCT among patients with HbS genotype. e mean cell volume recorded in this study was high, supporting the known fact that MCV usually is high in SCD patients due to the increasing need of erythropoiesis in response to chronic hemolysis leading to macrocytosis [27].…”
Section: Discussionsupporting
confidence: 53%
“…A comparable outcome was recorded among akin participants in North Maharashtra, India, where low levels of Hb concentration, RBC count, and PCV was documented [25]. Likewise, Patel and colleagues [26] also reported significant low level of hemoglobin and HCT among patients with HbS genotype. e mean cell volume recorded in this study was high, supporting the known fact that MCV usually is high in SCD patients due to the increasing need of erythropoiesis in response to chronic hemolysis leading to macrocytosis [27].…”
Section: Discussionsupporting
confidence: 53%
“…A significant proportion of our patients had microcytic anemia. This observation has also been reported by authors in India, who associate it with martial deficiency, in a population of sickle cell children from tribes and castes with a low socioeconomic level [33,34]. In our study, two findings support a more inflammatory origin: i) the demonstration of a statistically significant association between very high CRP levels and microcytosis; ii) the observation of a simple negative linear correlation, statistically significant (P = 0.003), between CRP levels and CMV.…”
Section: Discussionsupporting
confidence: 85%
“…This trend was also reported in a study of sickle cell children admitted to a tertiary hospital in India. Indeed, Patel et al reported a mean Hb level of 8.08 ± 2.40 g/dl with H of 23.34 ± 6.40% and CMV of 75.99 ± 2.12 µ 3 [33]. In Saudi Arabia, El-Ghany et al found a mean Hb level of 8.2 ± 1.5 g/dl (23), whereas we found a mean Hb level of 7.2 ± 1.9 g/dl, an H of 22.9 ± 7.7% and a CMV of 75.7 ± 10.1µ 3 .…”
Section: Discussionmentioning
confidence: 99%
“…A sample size of 100 subjects, consisting of previously diagnosed cases of SCA (SS pattern), was included in the study. The sample size was calculated using a previous study by Patel et al [ 6 ], which observed that out of 47 patients with sickle cell disease, 59.57% had an acute painful crisis, 25.53% had an acute febrile illness (AFI), 2.12% had acute chest syndrome, and 46.80% had severe anaemia. Taking this value as a reference, the minimum required sample size with a 10% margin of error and a 5% level of significance is 97 patients.…”
Section: Methodsmentioning
confidence: 99%